Mechanical and durability behaviour of roller-compacted concrete containing white cement by pass dust and polypropylene fibre. Issue 1 (2nd January 2022) - Ashteyat, Ahmed M.; Al Rjoub, Yousef S.; Murad, Yasmin; Asaad, Samaher
Abstract: This research investigates the potential use of waste white cement by pass dust (WCBPD) in producing roller-compacted concrete (RCC). Fifteen RCC mixes were casted in which cement was partially replaced by WCBPD at (10, 20, 30 and 40%) with addition of polypropylene fibre in two percents (0.25 and 0.5%). The mechanical properties of RCC mixes were evaluated using compressive and splitting tensile strength, modulus of elasticity and ultrasonic pulse velocity. The durability behaviour was evaluated through water absorption, dynamic modulus of elasticity and freeze–thaw resistant. Test results have shown that Increasing WCBPD to 20, 30 and 40% repalcement of cement has degraded the mechanical properties of RCC mixes. Even though, all RCC mixes reached a compressive strength greater than 27.6 MPa except mix with 40% WCBPD replacement level. All RCC mixes have shown a satisfactory durability. The addition of PPF has improved the mechanical and durability properties of RCC mixes with WCBPD. It is recommended to use waste WCBPD in producing RCC for up to 30% as a main base layer. Using WCBPD (as a replacement of cement) in producing RCC will effectively reduce the production cost and reduce environmental pollution by decreasing the disposal of this waste material in landfills.